YouTube®: An ally or an enemy in the promotion of living donor kidney transplantation?. (March 2018) - Bert, Fabrizio; Gualano, Maria Rosaria; Scozzari, Gitana; Alesina, Marta; Amoroso, Antonio; Siliquini, Roberta
The aim of the study is to evaluate the availability and accuracy of the existing Italian-language medical information about living donor kidney transplantation on YouTube®. For each video, several data were collected, and each video was classified as "useful, " "moderately useful" and "not useful." Globally, the search resulted in 306 videos: 260 were excluded and 46 included in the analysis. The main message conveyed by the video was positive in 28 cases (60.9%), neutral in 16 (34.8%) and negative in 2 (4.4%). The mean amount of visualizations was 3103.5 (range: 17–90, 133) and the mean amount of "likes" 2.7 (range: 0–28). Seven videos (15.2%) were classified as "useful, " 21 (45.7%) as "moderately useful" and 18 (39.1%) as "not useful." This study showed that a very few videos in Italian about living donor kidney transplantation are available on YouTube, with only 15 percent of them containing useful information for the general population.